2019
DOI: 10.18632/aging.102089
|View full text |Cite
|
Sign up to set email alerts
|

D-ribose is elevated in T1DM patients and can be involved in the onset of encephalopathy

Abstract: Although many mechanisms have been proposed for diabetic encephalopathy in type 2 diabetes mellitus (T2DM), the risk factors for cognitive impairment in type 1 diabetes mellitus (T1DM) are less clear. Here, we show that streptozotocin (STZ)-induced T1DM rats showed cognitive impairment in both Y maze and Morris water maze assays, accompanied with D-ribose was significantly increased in blood and urine, in addition to D-glucose. Furthermore, advanced glycation end products (AGE), Tau hyperphosphorylation and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 93 publications
0
17
0
1
Order By: Relevance
“…By assessing the impact of D-ribose on human nonenzymatic glycosylation of myoglobin, Yamamoto and Yamamoto (49) determined that D-ribose may accelerate glycosylation of myoglobin and other proteins more efficiently than D-glucose. Yu et al (62) also suggested that the urine concentration of D-ribose in patients with type 2 diabetes was substantially higher than that of normal individuals, which also indicated high levels of D-ribose in the body of patients with diabetes. In addition, high D-ribose concentrations may also cause chronic diabetes complications by other means.…”
Section: Potential Hazards Of High Concentrations Of D-ribosementioning
confidence: 99%
See 2 more Smart Citations
“…By assessing the impact of D-ribose on human nonenzymatic glycosylation of myoglobin, Yamamoto and Yamamoto (49) determined that D-ribose may accelerate glycosylation of myoglobin and other proteins more efficiently than D-glucose. Yu et al (62) also suggested that the urine concentration of D-ribose in patients with type 2 diabetes was substantially higher than that of normal individuals, which also indicated high levels of D-ribose in the body of patients with diabetes. In addition, high D-ribose concentrations may also cause chronic diabetes complications by other means.…”
Section: Potential Hazards Of High Concentrations Of D-ribosementioning
confidence: 99%
“…Wang et al ( 72 ) also indicated that in alkaline environments, D-ribose may decompose to formaldehyde by the reverse aldol reaction, and that by determining the content of formaldehyde in various parts of mice, it was suggested that formaldehyde produced by D-ribose accumulates in the brain of the mice and that the accumulation of endogenous formaldehyde to pathological concentrations may lead to disturbance of consciousness and cognition. However, it was also hypothesized that accumulation of D-ribose-induced AGEs is an important means underlying the occurrence and development of diabetic encephalopathy ( 62 ). Han et al ( 65 ) reported that D-ribose glycosylation led to the accumulation of AGEs in the nervous system, leading to spatial cognitive impairment and astrocyte-mediated RAGE-dependent inflammation.…”
Section: Potential Hazards Of High Concentrations Of D-ribosementioning
confidence: 99%
See 1 more Smart Citation
“…Notably, abnormally high levels of D-ribose have been observed in both T1DM (Yu et al, 2019) and T2DM (Su and He, 2014). Since administration of D-ribose induces the yield of Aβ and hyper-phosphorylated tau in the brain (Wu et al, 2015(Wu et al, , 2019Li et al, 2020), D-ribose might be also important for induction of AD.…”
Section: Importance Of Common Modifiers Of Alzheimer's Disease and Tymentioning
confidence: 99%
“…КПГ представляют собой группу молекул числом более 20 [1,2], различных по своим свойствам, включая способность к аутофлуоресценции и образованию поперечных сшивок. КПГ являются важными патогенетическими факторами развития когнитивных нарушений (диабетическая энцефалопа-тия, конформационные болезни мозга) [3][4][5][6]. Структуры некоторых КПГ представлены на рисунке 1.…”
Section: Introductionunclassified